A blue dye-sensitized solar cell based on a covalently bridged oligothiophene chromophore. Issue 4 (27th January 2016) - Demeter, Dora; Melchiorre, Fabio; Biagini, Paolo; Po, Riccardo; Roncali, Jean
Graphical abstract: Abstract: Two quaterthiophenes with a terminal electron acceptor cyanoacrylic acid anchoring group have been synthesized to serve as metal-free sensitizers in titanium dioxide-based dye-sensitized solar cells (DSSCs). The covalent bridging of the acceptor group with the adjacent thiophene ring by an ortho -phenylene unit leads to a large red shift of the internal charge-transfer band and to a strong decrease in its relative intensity. As a consequence of these spectral modifications, the color of the dye changes from orange to blue both in solution and after chemisorption on titanium dioxide. A preliminary evaluation of the bridged dye in DSSCs shows that the production of the blue color is associated with a decrease of the conversion efficiency of the cell.